Birokrasi dan Korupsi di Indonesia dalam Perspektif Sejarah (Catatan Keprihatinan Seorang Muslim) - - Suwarno (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2006)
This paper aims to describe relation between corruption and bureaucracy in Indonesia by historical perspective. The writer explains concepts of bureaucracy, corruption, relation among bureaucracy corruption and democracy which then the presents corruption and bureaucracy in historical perspective (comparing colonial and post freedom era in Indonesia), and opinion of the writer as a Muslim. According to the writer, corruption is not Indonesian nation's culture. The problem of corruption is related with structure of Indonesian bureaucracy softly and turns on possibility rampant of corruption, Islamic concept of construction is very anti-corruption.